2018
DOI: 10.1002/maco.201810425
|View full text |Cite
|
Sign up to set email alerts
|

The effect of Nb on microstructure, mechanical, and corrosion behavior of low Mn, microalloyed δ‐TRIP steel; a comparative study

Abstract: The aim of the present study was to examine the feasibility of achieving a better combination of yield strength, ductility, and corrosion resistance of δ‐TRIP steel through the concept of microalloying. Three δ‐TRIP steels with different contents of Nb (0, 0.025, 0.076 wt%) were subjected to the microstructural, mechanical, and electrochemical examination. ASTM A283 and ASTM A516 steels were taken as comparative samples. The obtained results revealed a threefold increase in strength × ductility products of TRI… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
2
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 17 publications
0
2
0
Order By: Relevance
“…After that, the samples were cooled down to ambient temperature. It is notable that the IA temperature is selected based on the previous study by Gholami Shiri et al [4] who indicated that the IA temperature ranges between 734 and 845°C based on differential thermal analysis results.
Figure 1 Schematic illustration of the heat treatment procedure.
…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…After that, the samples were cooled down to ambient temperature. It is notable that the IA temperature is selected based on the previous study by Gholami Shiri et al [4] who indicated that the IA temperature ranges between 734 and 845°C based on differential thermal analysis results.
Figure 1 Schematic illustration of the heat treatment procedure.
…”
Section: Methodsmentioning
confidence: 99%
“…Transformation-induced-plasticity (TRIP) steels have been considered as a candidate for advanced energy materials owing to the outstanding combination of strength, ductility and high energy absorption as well as excellent fatigue properties [1-5]. It is known that the main phases that exist in the microstructure of TRIP steels involve ferrite, bainite, retained austenite and martensite [1].…”
Section: Introductionmentioning
confidence: 99%
“…Numerous articles in this context have studied the effects of alloying elements, [14][15][16][17] initial and evaluated microstructure, 18,19 heat-treatment processes, 18,20 and heating rate on the microstructure and mechanical properties. Conventional TRIP-assisted steel is produced by a two-stage heat-treatment process.…”
Section: Introductionmentioning
confidence: 99%